Culture and the university education, ecology, design - Barnett, Ronald 1947-; Bengtsen, Søren Smedegaard; Nørgård, Rikke Toft (London, UK Bloomsbury Academic, Bloomsbury Publishing Plc, 2022)
"Not long ago, it was understood that universities and culture were intimately related. However, to a large extent, that understanding has faded. Culture and the University confronts this situation. Written by three leading scholars of higher education and the philosophy of higher education, the book opens the debate about the cultural purpose of universities and higher education. The authors argue that the university should be and can be an institution of culture, of great cultural significance in the digital age, and exercise cultural leadership in society. This wide-ranging and polemic text addresses a range of subjects including environmentalism, citizenship, post-truth, the ethical implications of technology and feminist philosophy. The authors build on the work of key philosophers of the university from Aristotle, Nietzsche and Heidegger to Donna Haraway, Terry Eagleton and Martha C. Nussbaum to conceive of an entirely modern vision of the university. This is a must-read for anyone with an interest in the future of higher education and the university."--Provided by publisher.
Introduction -- 1. Whatever Happened to the University for Culture? -- Part I: -- Warring cultures and a universal culture -- (Ronald Barnett, University College London, UK) -- 2. The Cultural Crisis of the University -- 3. Culture Wars: Multiplication and (possible) Re-unification -- 4. A Common Culture -- No and Maybe -- 5. For the University and the World: a Culture of the Earth -- Part II: -- Designing for cultural places -- (Rikke Toft Nørgård, Aarhus University, Denmark) -- 6. Placeful Cultures and Cultural Places -- 7. The Atmospheric University and Cultural Atmospheres -- 8. Cultures for Collective Visioning and Future-Making -- 9. Future-Scaping Alternative Universities -- Part III: -- Within and beyond culture -- (S ø ren Bengtsen, Aarhus University, Denmark) -- 10. Higher Education as Cultural Formation -- 11. Cultural Leadership -- 12. The Indivisible -- 13. Beyond Culture -- Part IV: -- Dialogical Imaginings -- 14. University Culture as Force, Coexistence, Endeavour and Entanglement Rikke Nørgård -- 15. A University of One's Own S ø ren Bengtsen -- 16. An Ecological Culture for a Non-Comprehending World Ronald Barnett -- Endnote: Uniting the University and Even the Earth: the Twin Culture.
Keywords: Universities and colleges -- Philosophy; Postsecondary education -- Philosophy; Education, Higher -- Philosophy